2021
DOI: 10.3390/s21227733
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Low Density Lipoprotein—Comparison of Electrochemical Immuno- and Aptasensor

Abstract: An elevated level of low density lipoprotein (LDL) can lead to the cardiovascular system-related diseases, such as atherosclerosis and others. Therefore, fast, simple, and accurate methods for LDL detection are very desirable. In this work, the parameters characterizing the electrochemical immuno-and aptasensor for detection of LDL have been compared for the first time. An immunosensor has been designed, for which the anti-apolipoprotein B-100 antibody was covalently attached to 4-aminothiophenol (4-ATP) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 40 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…In this work, we applied 4-aminothiophenol (4-ATP) as a linker possessing a NH 2 group at the end for covalent immobilization of antibody–ferrocene conjugates. Recently, we have shown that 4-ATP immobilized on the surface of gold delivers NH 2 groups, which are beneficial for covalent immobilization of antibodies [ 31 ]. Other authors have also confirmed these phenomena [ 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we applied 4-aminothiophenol (4-ATP) as a linker possessing a NH 2 group at the end for covalent immobilization of antibody–ferrocene conjugates. Recently, we have shown that 4-ATP immobilized on the surface of gold delivers NH 2 groups, which are beneficial for covalent immobilization of antibodies [ 31 ]. Other authors have also confirmed these phenomena [ 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The procedure of cleaning the gold electrode surface was carried out following previously reported protocol [ 31 ]. After careful cleaning, the Au electrodes were dipped in an ethanolic solution of 1 mM 4-ATP overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Aptamers including oligonucleotides or peptides have characteristics of high reproducibility and high throughput. However, these immunosensors cannot detect the LDL subclasses at present ( Rudewicz-Kowalczyk and Grabowska, 2021 ).…”
Section: Detection Of Ldl Subclassesmentioning
confidence: 99%
“…Surface-reactive primary amino-groups present on the beads allow for receptors immobilization through amide bond formation with carbodiimide—activated carboxylic groups from antibodies. We recently proved that linkers possessing NH 2 groups are advantageous for covalent immobilization of antibody [ 17 ]. This phenomenon was confirmed by others as well [ 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The formation of immunocomplex between LDL and antibody leads to blocking the electron transfer between redox couple and electrode surface. Then, the redox signal changes depend linearly on LDL concentration [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In the other type of immunosensors, the redox label is either covalently and directly immobilized on the surface of electrode or covalently conjugated with receptor, e.g., an antibody.…”
Section: Introductionmentioning
confidence: 99%